Effect of surface structure on biomechanical properties and osseointegration - Lee, Baek-Hee; Lee, Changyang; Kim, Dae-Gun; Choi, Kuiwon; Lee, Kyu Hwan; Do Kim, Young (ELSEVIER SCIENCE BV, 2008)
The purpose of this study is to improve the bone-bonding ability between titanium implants and living bone through the control of geometric design and chemical compositions of an implant surface. We compared the tissue healing response and resulting implant stability for three surface designs by characterizing the histological and mechanical properties of the healing tissue around smooth-surfaced Ti-6Al-4V (SS), CP-Ti plasma-spray-coated (PSC), alkali- and heat-treated (AHT) implants. The implants were transversely inserted into a dog thighbone and evaluated at 4, 8, and 12 weeks. Histological examination indicated that initial matrix mineralization leading to osseointegration occurred more rapidly with the AHT implant. During the 4, 8. and 12 week healing periods, new bone on the surface of AHT implant showed denser growth than that on the SS and PSC implants. The more extensive tissue integration and more rapid matrix mineralization with the AHT implant were reflected in the mechanical test data, which demonstrated superior attachment strength and interfacial stiffness for the AHT implant after healing for 4, 8 and 12 weeks of healing because of the mechanical interlocking in the micrometer sized rough surface and the large bonding area between bone and implant caused by the nanosized porous surface structure. Histological and mechanical data demonstrate that with the appropriate surface design selection, bone bone-bonding ability can be improved and can induce acceleration of the healing response, thereby improving the potential for implant osseointegration. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: DENTAL IMPLANT SURFACES; SPRAY-COATED IMPLANTS; MECHANICAL STABILITY; TITANIUM IMPLANTS; BONE; OSTEOBLASTS; ATTACHMENT; COMPOSITE; METALS